Bronchoalveolar lavage for etiological diagnosis of childhood pneumonia - Kartikeswar, Gouda Ankula Kartikeswar; Rahman, Helina; Dutta, H. K.; satapathy, Amit Kumar (International Journal of Contemporary Pediatrics, 2019)
Background: Pneumonia is the most common cause of childhood morbidity and mortality in age group less than 5 years. Identification of causative organism is a real challenge in these children though many of them are responding to the first line antibiotics therapy. Isolation of the organism is of paramount importance those who fails to respond to first line therapy. The objective of this study was to determine the relative efficacy of Bronchoalveolar Lavage (BAL) over blood culture in finding out causative organisms of childhood non responder community acquired pneumonia and to study antibiotic-sensitivity pattern of causative organisms. Methods: BAL and blood culture was performed in 17 patients of age 2 months to 5 years with pneumonia or severe pneumonia. Lavage fluid was cultured and growth of organism 10000CFU/ml was considered positive. Blood culture was taken on the same day. Antibiotic sensitivity was tested. Results: BAL isolated the organism in 82.35% (n=14) cases out of 17 patients and in 11.76% (n=2) by blood culture (p=0.002). Streptococcus pneumoniae was the most common organism isolated (58.82% (n=10)), followed by K. pneumoniae (23.53% (n=4)). Antibiotic therapy was changed in 58.82% (n=10) cases according on culture report. Transient rise in temperature, tachycardia and tachypnea was noted after procedure but no major complication was associated with BAL. Conclusions: BAL fluid culture in childhood pneumonia has high diagnostic value and better efficacy over blood culture in isolating causative organism without increased risk of complication and decreases unwanted exposure to empiric antibiotic in children with community acquired pneumonia who did not respond to initial 1st line therapy.